Formulation of a protocol to evaluate the aerobic granulation potential (AGP) of an inoculum - Dayana Grisales Penagos; Jenny Rodríguez Victoria; Mateo Villarraga Manrique (MethodsX, 2022)
This paper proposes and develops a protocol for measuring the aerobic granulation potential of sludge, aiming to provide an affordable and simple alternative that can facilitate the development of aerobic granulation technology. In this sense, the protocol comprises a set of parameters and considerations that interact to create a controlled environment and stimulate cell population clustering. All of this is done in the context of procedural simplicity, low cost, and the speed at which results are obtained. The protocol is essentially a three-stage method: preparation of the substrate, adaptation of the inoculum, and implementation of the protocol. Simple parameters were measured to evaluate the granulation process: SVI, settling velocity, and morphological parameters. The protocol was validated according to optimal ranges and criteria previously established in the literature. For this purpose, an activated sludge inoculum from a domestic wastewater treatment plant was submitted to the protocol, obtaining an optimal response of the biomass (SVI5 =13.90 mL g−1, settling velocity= 25,79 m h−1, Diameter > 0.2 mm) in a relatively short time (7 d). The results show that this protocol can constitute a tool for evaluation and decision-making using traditional laboratory equipment and is applicable at different scales.